The hepatocyte IKK:NF-κB axis promotes liver steatosis by stimulating de novo lipogenesis and cholesterol synthesis - Andries Heida (Elsevier, 2021)
Objective: Obesity-related chronic inflammation plays an important role in the development of Metabolic Associated Fatty Liver Disease (MAFLD). Although the contribution of the pro-inflammatory NF-κB signaling pathway to the progression from simple steatosis to non-alcoholic steatohepatitis (NASH) is well-established, its role as an initiator of hepatic steatosis and the underlying mechanism remains unclear. Here, we investigated the hypothesis that the hepatocytic NF-κB signaling pathway acts as a metabolic regulator, thereby promoting hepatic steatosis development. Methods: A murine model expressing a constitutively active form of IKKβ in hepatocytes (Hep-IKKβca) was used to activate hepatocyte NF-κB. In addition, IKKβca was also expressed in hepatocyte A20-deficient mice (IKKβca;A20LKO). A20 is an NF-κB-target gene that inhibits the activation of the NF-κB signaling pathway upstream of IKKβ. These mouse models were fed a sucrose-rich diet for 8 weeks. Hepatic lipid levels were measured and using [1–13C]-acetate de novo lipogenesis and cholesterol synthesis rate were determined. Gene expression analyses and immunoblotting were used to study the lipogenesis and cholesterol synthesis pathways. Results: Hepatocytic NF-κB activation by expressing IKKβca in hepatocytes resulted in hepatic steatosis without inflammation. Ablation of hepatocyte A20 in Hep-IKKβca mice (IKKβca;A20LKO mice) exacerbated hepatic steatosis, characterized by macrovesicular accumulation of triglycerides and cholesterol, and increased plasma cholesterol levels. Both De novo lipogenesis (DNL) and cholesterol synthesis were found elevated in IKKβca;A20LKO mice. Phosphorylation of AMP-activated kinase (AMPK) - a suppressor in lipogenesis and cholesterol synthesis - was decreased in IKKβca;A20LKO mice. This was paralleled by elevated protein levels of hydroxymethylglutaryl-CoA synthase 1 (HMGCS1) and reduced phosphorylation of HMG-CoA reductase (HMGCR) both key enzymes in the cholesterol synthesis pathway. Whereas inflammation was not observed in young IKKβca;A20LKO mice sustained hepatic NF-κB activation resulted in liver inflammation, together with elevated hepatic and plasma cholesterol levels in middle-aged mice. Conclusions: The hepatocytic IKK:NF-κB axis is a metabolic regulator by controlling DNL and cholesterol synthesis, independent of its central role in inflammation. The IKK:NF-κB axis controls the phosphorylation levels of AMPK and HMGCR and the protein levels of HMGCS1. Chronic IKK-mediated NF-κB activation may contribute to the initiation of hepatic steatosis and cardiovascular disease risk in MAFLD patients.